DINAMIKA RELASI ANTARA PRINSIP NON INTERFERENCE DAN PRINSIP SOLIDARITAS ASEAN - Gautama Budi Arundhati (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
In fact, the principle of solidarity had been tested in the dispute of South China Sea over the years. Nowadays, ASEAN have the charter, the ASEAN Charter, which had a striking feature concerning the implementation of the principle on the Article 41 Paragraph 4 ASEAN Charter. However, the involvement of ASEAN in its efforts to resolve the South China Sea dispute peacefully seems ineffective. In other words,the South China Sea dispute is not able to prove the existence of the principle of solidarity yet in ASEAN, so it seems that the structure of ASEAN in the between member states are such a loose knit structure,the three pillars of ASEAN is a key pillar in the development of ASEAN is not strong enough to build the ASEAN solidarity. ASEAN in many ways is different from the European Union which has the strong principle of solidarity that not limited only to the relationship between Member States alone, but also among the public, members and the community,or generations. This problem leads to the emerging bigger problem ASEAN potentially, therefore the principle of solidarity should be dealt with in more detail and covers various aspects. Keywords: the Principle of Solidarity, ASEAN, European Union